دور التدقيق الداخلي في الحد من مخاطر نظم المعلومات المحاسبية - هارون, بلابل; يونس, جبلون; عبد المالك, ديدي (جامعة الوادي - University of Eloued, 2023)
ان هذه الدراسة تسعى إلى الوقوف على دور التدقيق الداخلي للحد من مخاطر نظم المعلومات المحاسبية مع محاولة التعرف وحصر هذه المخاطر، ولمعرفة كل ذلك وضعنا مجموعة من الفرضيات معتمدين في تحليلها على المنهجين الوصفي والتحليلي، وقد خلصنا من خلالها الى أن معظم العاملين بالمؤسسة يؤكدون على فعالية دور التدقيق الداخلي في المساهمة في الحد من المخاطر التي تهدد سلامة نظم المعلومات المحاسبية. "This study aims to examine the role of internal auditing in mitigating the risks of accounting information systems while identifying and categorizing these risks. To achieve this, we formulated a set of hypotheses and analyzed them using descriptive and analytical approaches, the results showed that the majority of employees in the organization acknowledge the effectiveness of internal auditing in contributing to the reduction of risks that threaten the integrity of accounting information systems. "
Keywords: التدقيق الداخلي، مخاطر نظام المعلومات المحاسبية.; internal auditing, risks of accounting information systems.